A critical juncture: promoting responsible innovation in the self-driving automobile sector while improving human factors - Battel, Kayli; Pearl, David (Frontiers in Industrial Engineering, 2024)
Navigating the future of autonomous vehicles (AVs) brings promise and peril. This paper zeroes in on Tesla's innovative yet sometimes controversial approach to AVs, spotlighting the intersection of human cognition, vehicle automation, and safety. Amid the excitement of rapid tech advancements, we highlight the risks of over-reliance and potential misperceptions fueled by marketing overreach. Introducing the "Quick Car Scorecard," we offer a solution to empower consumers in deciphering AV usability, bridging tech specs with real-world needs. As AVs steer our future, it's crucial to prioritize human life and responsible innovation. The journey to automation demands not just speed, but utmost caution and clarity.